The Texan Star: The Story of a Great Fight for Liberty - Altsheler, Joseph A. (Joseph Alexander), 1862-1919 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Texan Star: The Story of a Great Fight for Liberty" by Joseph A. Altsheler is a historical novel written in the early 20th century. The story focuses on the Texan struggle for independence against Mexican rule, highlighting pivotal events and key figures like Stephen Austin and the young Edward Fulton. This tale captures the dramatic fight for liberty and the courage displayed by individuals in the face of oppression. The opening portion introduces readers to the confinement of Stephen Austin and Edward Fulton in a Mexican prison. Here, they reflect on the political tensions between Texas and Mexico, particularly the threat posed by General Santa Anna. Despite being imprisoned, both characters display resilience, with young Ned's longing for freedom driving him to consider an escape. The narrative sets a tone of urgency and determination, showcasing the personal stakes intertwined with broader historical upheaval while establishing the complex interplay between characters as they navigate this challenging landscape. (This is an automatically generated summary.)
Release date is 2005-05-18
E-text prepared by David Garcia, Emmy, and the Project Gutenberg Online Distributed Proofreading Team (www.pgdp.net) from page images generously made available by the Kentuckiana Digital Library (http://kdl.kyvl.org/)
Keywords: Texas -- Fiction